Phytochemical Screening and comparison of antibacterial assays of pimpinella anisum through extraction - Rakhshanda, Shagoofa (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Biotechnology, 2015.